ANALYSIS OF BEHAVIORAL PATTERN OF MANADO YOUNG INDIVIDUAL INVESTORS IN STOCK MARKET - Tulende, Sharell S. M.; Tumbuan, Willem J. F. A.; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
This study aims to identify the behavioral biases and behavioral pattern of Manado young individual investors in stock market. The qualitative approach has used in this research in order to observe and understand how the investors behave. The sample in this research are 15 Manado young individual investors (long-term and short-term investors) who have been involve in stock market for a minimum one-year experience, with the age range of 19 – 24 years old. The results of this study find that most of the young individual investors in Manado unconsciously apply the confirmation bias, overconfidence, and disposition effect. The endowment effect, self-attribution, and anchoring are also detected but not showing up too frequent. The hindsight, status-quo, narrative fallacy, and herding effect are undetected. Therefore, it shows that the behavioral pattern of Manado young individual investors are adaptive and independent. In addition, this research also identify the relationship between overconfidence and confirmation bias.Keywords: behavioral pattern, young individual investors, investor psychology, overconfidence, confirmation